Determinants of COVID-19 Vaccine Hesitancy: A Cross-Sectional Study on a Mexican Population Using an Online Questionnaire (COV-AHQ) - Delgado-Gallegos, Juan Luis; Padilla-Rivas, Gerardo R.; Zúñiga-Violante, Erika; Avilés-Rodríguez, Gener; Arellanos-Soto, Daniel; Gastelum-Arias, Lilia Julieta; Franco Villareal, Héctor; Cosío-León, María de los Ángeles; Romo-Cardenas, Gerardo Salvador; Moreno-Treviño, María G.; Moreno-Cuevas, Jorge E.; Islas, Jose Francisco (Frontiers in Public Health, 2021)
Mexico has become one of the most highly affected countries by the COVID-19 pandemic in Latin-America. Therefore, efficient vaccination programs are needed to address the pandemic. Although recent advances around the world, have made it possible to develop vaccines in record time, there has been increasing fear and misinformation around the vaccines. Hence, understanding vaccine hesitancy is imperative for modelling successful vaccination strategies. In our study, we analyzed the attitude and perceptions towards COVID-19 vaccination, in a Mexican population (n=1512), using the proposed COV-AHQ (Cronbach alpha >0.8), which evaluates, danger and contamination regarding COVID-19, xenophobia generated throughout the COVID-19 quarantine, fear of COVID-19 vaccination adverse effects, and parent’s hesitancy towards children’s vaccination, furthermore a section including sociodemographic variables was included. According to the results of our study, the statistical correlation analysis of the general vaccination posture, seems to correlate significantly (p < 0.05) with mild perception of danger and contamination and a moderate perception of xenophobia, hesitancy towards children vaccination, willingness to get COVID-19 vaccine, previous influenza vaccination, perception the vaccine could help the country’s economy, occupation, gender, age, and participants actively researching COVID-19 vaccine information. An in-depth analysis assisted by binary logistic regression, concluded that the young adult population around ages 18-34 are the most likely to get vaccinated. This posture seems to be highly influenced by the perception of danger and contamination of the virus, xenophobia, fear of adverse effects and parents’ attitude towards child vaccination. While their own personal religious beliefs, economic status, the level of education does not seem to have an effect on the willingness to get vaccinated, neither did having a previous COVID-19 diagnosis or even knowing someone with a positive COVID-19 diagnosis. Health authorities and policymakers could use the results of the study to aid in modeling vaccination programs and strategies and identify population groups with high vaccine hesitancy prevalence and assess significant public health issues.